2018
DOI: 10.13057/biodiv/d190141
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of colubrid snakes based on 12S rDNA reveals distinct lineages of Dendrelaphis pictus (Gmelin, 1789) populations in Sumatra and Java

Abstract: Nugraha FAD, Fatchiyah F, Smith EN, Nia Kurniawan N. 2018. Phylogenetic analysis of colubrid snakes based on 12S rDNA reveals distinct lineages of Dendrelaphis pictus (Gmelin, 1789) populations in Sumatra and Java. Biodiversitas 19: 303-310. The phylogenetic relationship among the major colubrid snakes, particularly those of the subfamily Colubrinae, has been the subject of much debate. Also, there was limited data on the molecular relationships of Sundaland colubrid snakes. This study aimed to examine the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The divergence time estimates indicated that the genus Ahaetulla started to diverge as A. prasina and A. mycterizans in the late Oligocene, approximately 24.9 Ma. Our results were in agreement with those of Nugraha et al (2018) that the subfamily Ahaetullinae diversified during the late Oligocene, at about 24 Ma. The late Oligocene was the period when Sunda Shelf lakes were connected to the sea and were brackish, which may have facilitated many migrations of terrestrial fauna (Hall, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The divergence time estimates indicated that the genus Ahaetulla started to diverge as A. prasina and A. mycterizans in the late Oligocene, approximately 24.9 Ma. Our results were in agreement with those of Nugraha et al (2018) that the subfamily Ahaetullinae diversified during the late Oligocene, at about 24 Ma. The late Oligocene was the period when Sunda Shelf lakes were connected to the sea and were brackish, which may have facilitated many migrations of terrestrial fauna (Hall, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Malang, East Java KY700863 (Nugraha et al, 2018) Ptyas mucosa Malang, East Java KY700867 (Nugraha et al, 2018) using MrBayes software (Ronquist and Huelsenbeck, 2003) using Markov Chain Monte Carlo (MCMC) estimated for 5 million generations. The most appropriate sequence evolution models were selected using Akaike Information Criterion (AIC) for ML and BI.…”
Section: Dendrelaphispictusmentioning
confidence: 99%
See 2 more Smart Citations
“…A notable exception is represented by the specimens GA 328 and GA 329, which are here reported as U. prope guentheri ( Table 1 ) based on their maximum identity score (96.8%) with a previously deposited homologous sequence of U. guentheri , (AN EU596688). Considering the pairwise distance threshold usually used for species identification in squamates for the 12S (3–4%) see e.g., [ 30 , 31 ], it is therefore possible that the samples GA 328 and GA 329 represent an undescribed lineage of Uroplatus , but more focused morphological and molecular analyses employing a combination of mitochondrial and nuclear markers should be performed to better assess the taxonomic placement of these samples. This result is not surprising considering the significant number of newly described Uroplatus species in the last years and the molecular identification of different undescribed lineages (e.g., [ 20 , 23 ]).…”
Section: Methodsmentioning
confidence: 99%